Parental investments and children's human capital in low-to-middle-income countries - Behrman, Jere Richard, 1940- (Cambridge elements. Elements in development economics, 2022)
This Element reviews what we know about parental investments and children's human capital in low-to-middle-income countries (LMICs). First, it presents definitions and a simple analytical framework; then discusses determinants of children's human capital in the form of cognitive skills, socioemotional skills and physical and mental health; then reviews estimates of impacts of these forms of human capital; next considers the implications of such estimates for inequality and poverty; and concludes with a summary suggesting some positive impacts of parental investments on children's human capital in LMICs and a discussion of gaps in the literature pertaining to both data and methodology. This title is also available as Open Access on Cambridge Core.